2002
DOI: 10.1055/s-2002-20438
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Reconstruction of the Stomatal Complex in Pinus canariensis Needles Using Serial Sections

Abstract: The three‐dimensional (3D) morphology of the stomata in leaves of Pinus canariensis is described with respect to the spatial arrangement of guard cells, subsidiary cells, polar and lateral cells. Serial semi‐thin sections of the stomatal apparatus were digitally reconstructed and analysed with regard to the position, shape and size of the cell types involved. The stomatal complex consists of 16 cells with uniquely shaped polar and lateral cells. The polar cells form a kind of roof above the epistomatal chamber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Wild-type plants also displayed unstacked thylakoids when grown under restricted watering (Fig. 4C), which is a typical response of chloroplasts to water stress (Sestak and Pospisilova, 1986;Zellnig et al, 2002). Notably, the parenchyma cells of P SARK ::IPT transgenic plants displayed an intracellular arrangement where chloroplasts, mitochondria, and peroxisomes were consis- ).…”
Section: Ck-dependent Photorespirationmentioning
confidence: 84%
“…Wild-type plants also displayed unstacked thylakoids when grown under restricted watering (Fig. 4C), which is a typical response of chloroplasts to water stress (Sestak and Pospisilova, 1986;Zellnig et al, 2002). Notably, the parenchyma cells of P SARK ::IPT transgenic plants displayed an intracellular arrangement where chloroplasts, mitochondria, and peroxisomes were consis- ).…”
Section: Ck-dependent Photorespirationmentioning
confidence: 84%
“…However, within the same species, or between species with comparable stomata morphology, an increase in stomatal density will improve stomatal control. As Zellnig et al (2002) showed, P. canariensis has highly specialized stomata compared to other pine species.…”
Section: Discussionmentioning
confidence: 99%
“…Stomatal morphology of P. canariensis reflects adaptation to strict control of water loss. Stomata are deeply inserted (Jimenez et al 2000) and elongated prestomatal cavities filled with epicuticular waxes restrict water loss (Zellnig et al 2002). Furthermore, stomata are small compared to other pine species, such as P. sylvestris (Crossley & Fowler 1986;Turunen & Huttunen 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The natural distribution area is small, restricted to a volcanic Archipelago near to the African continent, but with remarkable ecological variation due to topography and the variable influence of Trade winds (Climent et al 2004). While needle anatomy and surface characteristics of this species has been described in detail both for juvenile and mature needles (Jiménez et al 2000;Zellnig et al 2001;Stabentheiner et al 2004), geographical phenotypic variation in needle anatomy and morphology is still unknown. Previous studies have detected significant differentiation among populations in survival (López et al 2007), ontogeny (Climent et al 2006), traits related to fire adaptation (Climent et al 2004) and cone morphology .…”
Section: Introductionmentioning
confidence: 99%